HUBUNGAN MENARCHE USIA DINI DAN MENOPOUSE USIA LANJUT DENGAN KEJADIAN PENYAKIT KANKER PAYUDARA - Jannah, Miftahul; Septiani, Suci; Holiday, Evi (JOURNAL OF HEALTH SCIENCE, 2021)
Cancer is a disease of cell growth, resulting from damage to genes that regulate cell growth and differentiation. One of the causes of such damage is gene mutation. Sometimes it grows uncontrollably and forms a lump, when the abnormal lump continues to grow and become malignant. One of the most common cancers affecting women is breast cancer. Breast cancer can actually attack men, but this is rare. Women are a hundred times more likely to get breast cancer than men. This research is a quantitative research with an analytical survey with a cross sectional approach. The population in this study were all mothers with cancer, totaling 273 people. The sample of this research used systematic random sampling method. The sample of this study amounted to 73 respondents. Data analysis was carried out in two stages, namely univariate analysis and bivariate analysis with Chi-square statistical test. The results of the bivariate analysis showed that there was a relationship between early menarche (p value = 0.03) and there was a relationship between early breast cancer (p value = 0.03) and early menopause. The advice given is input to further improve facilities, especially the midwifery department in providing standardized care for mothers with breast cancer and health monitoring, especially for mothers who have risk factors. Keywords: Breast Cancer